2012
DOI: 10.1039/c2jm31112g
|View full text |Cite
|
Sign up to set email alerts
|

Size- and surface chemistry-dependent intracellular localization of luminescent silicon quantum dot aggregates

Abstract: Aggregates of luminescent silicon quantum dots (Si-QDs) selectively label certain organelles, such as lysosomes, endoplasmic reticulum, cytosol and nuclei, depending upon the size of the aggregates and their surface properties. We used Si-QDs in an aggregated form and the size of aggregates was controlled from ca. 30 to 270 nm diameter. In fixed human umbilical vein endothelial cells (HUVECs), allylamine-terminated Si-QDs selectively labeled cell nuclei, while Si-QDs, treated by the amphiphilic block copolymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 53 publications
(64 reference statements)
0
29
0
Order By: Relevance
“…Of these characteristics, the particle size is a crucial factor which determines NP endocytosis pathway [17,18], uptake rate and efficiency [6,16,[19][20][21][22], in vitro cytotoxicity [23][24][25][26][27][28], immune responses [27][28][29][30], and the final localisation [15,31,32]. Thus size-dependent uptake of various NPs has been intensively investigated and widely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Of these characteristics, the particle size is a crucial factor which determines NP endocytosis pathway [17,18], uptake rate and efficiency [6,16,[19][20][21][22], in vitro cytotoxicity [23][24][25][26][27][28], immune responses [27][28][29][30], and the final localisation [15,31,32]. Thus size-dependent uptake of various NPs has been intensively investigated and widely reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above-mentioned exciting progress, SiNPs-based probes were recently also used to specifically target certain organelles, such as lysosomes, endoplasmic reticulum (ER), cytosol, and nuclei [32,33]. For example, Ohta and coworkers demonstrated that lysosomes and ER could be selectively labeled by surface modified SiNPs [33].…”
Section: In Vitro Imagingmentioning
confidence: 98%
“…For example, Ohta and coworkers demonstrated that lysosomes and ER could be selectively labeled by surface modified SiNPs [33]. In their work, the as-prepared SiNPs were treated In particular, the SiNPs/protein bioconjugates specifically target microtubules exhibiting red fluorescence.…”
Section: In Vitro Imagingmentioning
confidence: 99%
“…275,276 Pluronic F127 was also used as a dispersing agent for Si NCs produced by laser pyrolysis and capped with ethyl undecylenate. Luminescent and stable micelles were produced without preventive covalent surface capping of the Si NCs.…”
Section: Non-covalent Functionalizationmentioning
confidence: 99%
“…This method produced Si NC aggregates able to selectively label the endoplasmic reticulum (ER) in live cells. 276 In particular, size of the aggregates was controlled from ca. They form, in water, micelles where the PPG core constitutes a low polar nano-environment.…”
Section: Si Qds From the Plasma-assisted Processmentioning
confidence: 99%